Transmission dynamics of Ebola virus disease with human mobility in Sierra Leone. (November 2017) - Li, Li
Abstract: Ebola virus disease outbreak in West Africa in 2014, especially serious in Sierra Leone. In order to reveal the transmission mechanisms of ebola virus disease, we present a mathematical model to estimate the basic reproduction number in Sierra Leone. It was found that if effective control strategies are not taken, then ebola virus disease will outbreak in Sierra Leone. What is more, it was revealed that human mobility may paly an important role on the outbreak of ebola virus disease.